Administração experimental de esteróide anabólico androgênico e álcool causa alterações histológicas e morfométricas nos ovários e útero de ratas adultas - Camargo, Isabel Cristina Cherici [UNESP]; de Gênova, Tatiana Cristina [UNESP]; Machado, Marcela Cristina de Pontes [UNESP]; Frei, Fernando [UNESP]; Mesquita, Suzana de Fátima Paccola (My University, 2011)
Abusive and indiscriminate use of androgenic anabolic steroid is an usual practice among youth and adults of both sex. Usually these substances were utilized simultaneously with others drugs, licit or not, that causes damage to health. The purpose of study was to evaluate the influence of experimental administration of nandrolone decanoate steroid (ND), associated or not to alcohol, in the ovaries and uterus of adult rats. Females with regular estrous cycle (n = 20), were distributed in the groups: a) control (physiological solution); b) ND (7.5 mg/kg BW; intraperitoneal); c) alcohol (0.2 mL/100g BW; oral); d) ND + AL. The teatments were realized by single dose per week, during twelve consecutive weeks. The ovaries of rats in the groups ND, AL and ND + AL presented intense follicular atresia and decrease in the number of antral follicles and corpora lutea. None treatment did affect ovarian weight, but uterine weight was increase (p<0.05) in the ND + AL group. There were alterations in the uterine histology and morphometry at function of each treatment. Isolated or simultaneous use of anabolic steroid and alcohol promotes ovarian and uterine toxicity in adult female rats.
Experimental administration of anabolic androgenic steroid and alcohol causes histological and morphometrical alterations in the ovaries and uterus of adult rats
Keywords: Alcohol; Anabolic steroid; Histomorphometry; Ovaries; Rats; Uterus